Reflection of Semiotics in Pictographic Signs - Quraqova Shoxida Dagar qizi; Bahrom Jabborov (Academia One, 2023)
Semiotics permeates the realm of icons, shaping their meanings and influencing how they are interpreted. Icons serve as powerful visual symbols, cultural signifiers, and communicative tools that rely on semiotic principles to convey meaning effectively and efficiently. This article reflects on the relationship between semiotics and pictograms and discusses the reasons for cross-cultural differences in pictographic images.
Keywords: Icon; semiotics; image